Self within marriage : the foundation for lasting relationships - Zeitner, Richard M. (New York : Routledge, 2011)
'Self Within Marriage combines the theoretical orientations of object-relations theory, self psychology, and systems theory to illustrate and discuss a way of understanding and working with couples and individuals whose relationship and emotional difficulties have centered on the very common conundrum of balancing individuality and intimacy in romantic relationships. Based on detailed case examples and couples therapy techniques, Self Within Marriage provides individual and analytic therapists with a refreshing new framework for working with clients and for helping them understand who they are as individuals and as partners'--
Keywords: Marital Therapy; Couples Therapy